LITERATURE REVIEW ON COGNITIVE FLEXIBILITY IN THE FIELD OF BUSINESS MANAGEMENT AND ACCOUNTING USING THE SCOPUS DATABASE - Shalahuddin, Shalahuddin; Hasyim, Budi; Hasanah, Nurjannatul; Nursia, Nursia; Suryaningsih, Suryaningsih (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to examine the development of research on cognitive flexibility in the fields of business management and accounting through a bibliometric approach based on data from the Scopus database. Cognitive flexibility is understood as an individual’s ability to shift perspectives and adapt responses to situational dynamics, which is crucial in modern managerial decision-making. The analysis was conducted on 166 documents published between 1989 and 2025. The results show a significant increase in publication volume since 2019, with research articles dominating (98.8%). The journal that most frequently published related articles is the Journal of Business Research, while the most productive author is Septianto, F. The largest contributions come from institutions in the United States, China, and Australia. The subject areas are dominated by Business, Management and Accounting (45.5%), followed by Social Sciences and Psychology. These findings indicate that cognitive flexibility is an increasingly global and interdisciplinary topic, with great potential for further development in the context of strategic management, organizational innovation, and human resource development.